Cooperative learning “three-steps-interview” to enhance students’ speaking skill from the perspective of students’ creativity - Novitasari, Putri Novitasari (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
The aim of this research is to find out whether: (1) cooperative learning three-steps-interview is more effective than direct method for the 11th grade  students; (2) students having low creativity have better speaking skill than those having low creativity; and (3) there is an interaction between teaching methods and students’ creativity in teaching speaking skill for the 11th grade of SMAN 8 Kediri. This research was an experimental research conducted in SMA N 8 Kediri. The population was all the 11th grade of SMA N 8 Kediri. The researcher took the sample of the research by using cluster random sampling and devided the group into two. One became the experimental group taught using cooperative learning three-steps-interview and one another became the control group taught using direct method. The number of sample was arround of 60 students. The technique of the data collection was done by giving oral test for speaking skill and written test for verbal creativity test. After collecting the data of the research sample, further the data was analyzed using ANOVA 2x2 and Tukey formula to test the research hypothesis. The result of this research shows that: (1) cooperative learning three-steps-interview (TSI) is more effective than direct method (DM) to teach speaking skill for the 11th grade of SMA N 8 Kediri; (2) students having high creativity have better speaking skill than those having low creativity; and (3) there is an interaction between teaching methods and students’ creativity to teach speaking skill for the 11th grade of SMA N 8 Kediri. At last, it is recomended that: (1) teacher should apply cooperative learning three-steps-interview (TSI) to teach speaking skill; (2) the students should apply three-steps-interview to explore their speaking skill; and (3) other researchers should make such an improvement by trying to use this research topic with different subject of the research and different psychological point of view besides creativity which may have correlation with students’ speaking skill.